EFEK EKSTRAK BUAH NAGA MERAH (Hylocereus polyrhizus) TERHADAP GAMBARAN HISTOPATOLOGI GLOMERULUS GINJAL PADA TIKUS PUTIH (Rattus novergicus) YANG DIINDUKSI PANGAN TINGGI LEMAK MODEL DISLIPIDEMIA - Tasya Tamaya (2021)
Acute kidney injury (AKI) is a rapid decrease (in hours to weeks) of glomerular filtration rate (GFR) which is generally reversible, followed by failure of the kidneys to excrete nitrogen metabolic waste, with / without disturbed fluid and electrolyte balance, and one of the risk factors for Kidney damage can be caused by the presence of ROS (Reactive oxygen specs) which can be formed in food through lipid oxidation from excessive intake of foods containing fat.The design of this study was a true experiment by dividing 30 male white rats into 5 treatment groups. (1) Negative control, (2) Positive control (quail eggs), (3) Experiment 1 (simvastatin), (4) Experiment 2 (Hylocereus polyrhizus extract at a dose of 60 mg / day for 8 weeks), (5) Experiment 3 (extract Hylocereus polyrhizus at a dose of 60 mg / day for 16 weeks). Data was analyzed with One Way Anova and contunued with Pos Hoc Bonfferroni, In Hylocereus polyrhizus extract group for 8 weeks, there was a significant decrease in renal glomerular histopathological damage (P-value <0.05), while in the 16-week Hylocereus polyrhizus extract group there was no significant result of rats glomerular histopathological description (P-value> 0.05) when compared to the positive control group, which is caused by the degradation of betasianin and flavonoids due to heating in the manufacture of dragon fruit extract, the heating process in any form of dragon fruit extract can reduce the antioxidant levels of the extract,so the longer it takes will be the lower the antioxidants, and the effective feeding time of dragon fruit (Hylocerus polyrhizus) is better before comsuming any form of meal. So the conclusion is induction of high-fat feed has an effect on histopathological changes in renal glomerular of white rats, red dragon fruit extract has an effect on preventing the process of renal glomerular damage to white rats, administration of dragon fruit extract and simvastatin for 8 weeks does not show a significant effect on effectiveness in maintaining kidney health, and administration 16 weeks of red dragon fruit extract showed a decrease in effectiveness compared to 8 weeks of red dragon fruit extract.